PARAFRASA DALAM TERJEMAHAN NOVEL PEEBEE HAS A WISH - Arif Hidayat; Danang Dwi Harmoko (RETORIKA: Jurnal Bahasa, Sastra, dan Pengajarannya, 2018)
Abstract. Paraphrases in the Novel Translation Peebee Has a Wish. This study will bring a new dimension to translation study where many researches have discussed about techinques, strategies, and procedures in translation. This study is aimed at giving explanation of how paraphrase is used in the process of translation by translator in a literary work Harapan Peebee from its original version ‘Peebee Has A Wish’ based on the theory of Danielsson which divide the level of equivalence on the lexical, phrase and grammar alternatives. This study uses descriptive qualitative method. The result shows that the three alternatives categories are found in the translation. Meanwhile, phrase category dominates the findings. However, there are many findings tell the overrated paraphrases where one utterance or sentence are inhabited by more than one alternatives or even all of the categories mentioned by Danielsson.